Remote teaching & digital platform during pandemic Teacher education and teacher competence effects among teachers & principles in Malaysia - RAMANLINGAM, SHANTI (Advances in Social Sciences Research Journal, 2021)
The purpose of this research is analyzing the opportunities and challenges of emergency remote teaching based on experiences of the COVID-19 emergency among teachers and principals of Malaysian schools. This study explores the perceptions of school teachers of online learning in a program developed in Malaysian school called School from Home during the COVID-19 Pandemic. A qualitative research method was undertaken in two steps. In the first step, a thematic analysis a qualitative method was used based on a two-step process. The first step consisted a Qualitative study which involved 4 school principals from Grade A and Grade B schools which is selected from four state which is Selangor, Johor, Kedah and Kelantan. In the second step (a Malaysian case study), The results from the interview discussion represented the basis for the second step, in which starting from the main issues that emerged from the online discussion among researches, professors and also Higher Education Offices from Ministry of Education and State Education Officers. The analysis reveals several technological, pedagogical and social challenges. The technological challenges are mainly related to the unreliability of Internet connections and many students’ lack of necessary electronic devices. (Chandler. D, 2017) The pedagogical challenges are principally associated with teachers’ and learners’ lack of digital skills, the lack of structured content versus the abundance of online resources, learners’ lack of interactivity and motivation and teachers’ lack of social and cognitive presence (the ability to construct meaning through sustained communication within a community of inquiry) (Gordon, 2020) The social challenges are mainly related to the lack of human interaction between teachers and students as well as among the latter, the lack of physical spaces at home to receive lessons and the lack of support of parents who are frequently working remotely in the same spaces. Based on the lessons learned from this worldwide emergency, challenges and proposals for action to face these same challenges, which should be and sometimes have been implemented, are provided.